Susac syndrome: clinical characteristics, clinical classification, and long-term prognosis. Issue 43 (October 2016) - Vishnevskia-Dai, Vicktoria; Chapman, Joav; Sheinfeld, Roee; Sharon, Tal; Huna-Baron, Ruth; Manor, Riri S.; Shoenfeld, Yehuda; Zloto, Ofira
Abstract : Abstract: Susac syndrome is a rare condition characterized by the clinical triad of central nervous system (CNS) dysfunction, sensorineural hearing impairment, and branch retinal artery occlusion (BRAO). The purpose of this study is to examine the demographics, clinical characteristics, treatment, and long-term prognosis of Susac syndrome. The data recorded for all Susac syndrome patients treated at the Sheba Medical Center between 1998 and 2014 included demographics, clinical signs at presentation and during the disease course, imaging findings, treatment, and prognosis. Susac syndrome was diagnosed in 10 patients (age range 30–45 years). Only 2 patients presented with the full triad and 7 patients developed the full triad during mean follow-up period of 35 months. The average time to full triad was 7 months. Based on our observations at presentation, we divided the disease course into suspected, incomplete, and complete Susac syndrome. All 10 patients were treated at diagnosis with a pulse of high-dose intravenous methylprednisolone. There was improvement in visual acuity and visual field at the end of follow-up compared to baseline, but it was not statistically significant ( P = 0.479 and P = 0.053, respectively). Five patients remained with neurological damage, and 5 patients had no improvement of their hearing loss at study closure. In conclusion, Susac syndrome is a rare condition that can mimic other disorders. The diagnosis is challenging because most patients do not initially present with the definitive triad. We suggest a clinical classification for the syndrome that may assist in early diagnosis.